Glacier discovery and their studies in the mainland Northern Eurasia - V. M. Kotlyakov; L. P. Chernova; N. M. Zverkova; T. E. Khromova (Лëд и снег, 2015)
The history of studies of ten mountain glacier systems in Russian Subarctic is analyzed in the paper (Fig. 1). The intensity of these systems reduction and the vertical extent of glaciers during last 150 and 50 years are compared with the climate warming in this part of Russia, the map of accumulation–ablation on glaciers of this region is given (Fig. 3). Very quick reaction of the glacier surface to climatic changes is shown. The precision of glaciers’ size during 1960–1980 and 2000 are estimated and suggestion for future monitoring of glaciers size is made.